SELF EXAMINATION OF BREAST - A STUDY ON MASTECTOMY PATIENTS - Abayadeera, A.; De Zoysa, M.I.M.; De Silva, S.K.L.A. (My University, 2012)
Self examination of breast (SEB) is a well accepted method for early detection of breast cancer. The risk of developing a recurrence at the mastectomy site or a malignancy in the remaining breast is high in patients who have already had a breast cancer and the role of SEB in these patients cannot be challenged. The study aimed to assess the knowledge and practice of SEB in post-mastectomy patients.